1998
DOI: 10.1037/0022-0167.45.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Applying social cognitive theory to interest in research among counseling psychology doctoral students: A path analysis.

Abstract: In this study, the R. W. Lent, S, D. Brown, and G. Hackett (1994) social cognitive model of interest development was applied to the prediction of interest in research. Participants included 184 counseling psychology doctoral students. Results of a path analysis indicated that 5 variables were significant predictors of interest in research: research outcome expectations, research self-efficacy beliefs, investigative interests, artistic interests, and age. In addition, several factors indirectly affected interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
185
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(213 citation statements)
references
References 20 publications
15
185
0
6
Order By: Relevance
“…College competence beliefs at the end of the first semester were also associated with persistence in the next semester, controlling for college competence beliefs on the first college day and other variables such as gender, ethnicity, first-generation status, and high school academic achievement (Wright, Jenkins-Guarnieri, & Murdock, 2012). In graduate students, perceived academic competence predicted later academic persistence (Losier, 1994), while in doctoral students, competence beliefs toward research have been associated with interest in the research (Bishop & Bieschke, 1998) and research productivity (e.g., number of submitted articles, conference presentations; Brown, Lent, Ryan, & McPartland, 1996;Hollingsworth & Fassinger, 2002).…”
mentioning
confidence: 99%
“…College competence beliefs at the end of the first semester were also associated with persistence in the next semester, controlling for college competence beliefs on the first college day and other variables such as gender, ethnicity, first-generation status, and high school academic achievement (Wright, Jenkins-Guarnieri, & Murdock, 2012). In graduate students, perceived academic competence predicted later academic persistence (Losier, 1994), while in doctoral students, competence beliefs toward research have been associated with interest in the research (Bishop & Bieschke, 1998) and research productivity (e.g., number of submitted articles, conference presentations; Brown, Lent, Ryan, & McPartland, 1996;Hollingsworth & Fassinger, 2002).…”
mentioning
confidence: 99%
“…Research interest was adapted from Bishop and Bieschke (1998) as cited in Vaccaro (2009). The tool was assessed by rating 11 items, with the 1-5 Likert scale as options (from 1 = not interested at all to 5 = very interested).…”
Section: Methodsmentioning
confidence: 99%
“…Research interest was chosen also due to its detected significant relationship with research attitude variables (such as research self-efficacy and research outcome expectation) and its roles in predicting research behaviors, all clearly revealed in another line of studies employing the Social Cognitive Theory (e.g. Bishop & Bieschke, 1998;Bard, Bieschke, Herbert, & Eberz, 2000). While those studies paid serious attention on the nexus between research interest and other variables, seemingly, there has yet to be an empirical examination of relationship between research interest and research intention.…”
Section: Research Intention: Theoretical and Empirical Basesmentioning
confidence: 99%
“…However, discussions on faculty's research interest and factors affecting it have been limited and mostly conducted in the context of developed and semi-developed countries (e.g. Bishop & Bieschke, 1998;Bard, Bieschke, Herbert, & Eberz, 2000;Lambie & Vaccaro, 2011). Those existing accounts fail to offer enough knowledge and thinking on this particular issue in the developing context of higher education.…”
Section: Rise -International Journal Of Sociology Of Education 4(3) 201mentioning
confidence: 99%
“…According to Kanh and Scott (1997), research interest was the key mediator that links personality types and research training environment to research productivity and career goals. Bishop and Bieschke (1998) correspondingly concluded: "Understanding the development of research interest is important precursor to building a testable, parsimonious model of research productivity." However, discussions on faculty's research interest and factors affecting it have been limited and mostly conducted in the context of developed and semi-developed countries (e.g.…”
Section: Rise -International Journal Of Sociology Of Education 4(3) 201mentioning
confidence: 99%